Evaluation of Sharp Force Injury Cases in Terms of Life Threatening Danger - Derkuş, Emir; Özkara, Erdem (The Bulletin of Legal Medicine, 2025)
Objective: Sharp tools, which are frequently used in daily life, are widely used in attacks and injuries due to ease of transportation. For this reason, injuries and deaths due to these tools are frequently observed in forensic medicine practices. The aim of our study was to evaluate sharp force injuries in terms of life-threatening risk and to determine the precautions that can be taken by drawing attention to violent incidents.Methods: Between 01.01.2015-31.12.2019, cases who underwent medicolegal evaluation due to sharp force injuries were evaluated in terms of sociodemographic information, injury sites, number of wounds, injury characteristics and severity. The findings were compared with similar studies.Results: 295 cases were evaluated in the study. 92.5% of the cases were male and 7.5% were female, and the most common age range was 21-30 years (31.2%). The thorax was the most commonly injured body region (24.2%). The rate of internal organ injury was 25.8%. In 66.1% of cases, the injury wasn’t cured with simple medical treatment, 6.1% had bone fractures and 34.2% were life-threatening.Conclusion: Sharp force injuries most frequently affect young adults and cause serious health problems, economic and labor losses. The easy availability of these tools and the fact that the law does’nt penalize the possession of knives used in the home, industry, agriculture or in a profession or art increase the incidents of violence. There is a need for stricter legal regulations, especially on the transportation of such tools.
Keywords: sharp force injuries; life threatening; forensic traumatology; firearm wounds